A hybrid model to assess the hydropower potential for rivers. (6th January 2021) - Al-Juboori, Anas Mahmood; Guven, Aytac
A computer program called hydropower plant site assessment program (HPSAP) was developed by using Visual Basic programming to assess the hydropower potential in river basins. A methodology to select the best site to install the hydropower plant was developed according to meteorological, hydrological and economical design criteria. HPSAP has several options to analyse watersheds for different head or power criteria. HPSAP estimates the locations coordinate and upstream drainage area for powerhouse and weir locations, elevation of powerhouse and weir, the distance between weir site and powerhouse site, penstock length, design head and power for proposed plants. The design discharge is estimated by using a flow duration curve regression equation developed by group method of data handling (GMDH) based on rainfall-runoff model outputs. The hydrological engineering centre-hydrological modelling system (HEC-HMS) model was used as the hydrological rainfall-runoff model in this study. The results have proven the ability of the program to assess the hydropower potential in river basins.